Hydrogen‐Bond‐Mediated Surface Functionalization of Boron Nitride Micro‐Lamellae toward High Thermal Conductive Papers. Issue 10 (25th February 2023) - Yu, Shulei; Liao, PeiChi; Zhang, Yilin; Li, Yifei; Tian, Huifeng; Li, Ruijie; Liu, Shizhuo; Yao, Zhixin; Li, Zhenjiang; Wang, Yihan; Zhang, Lina Yang; U, SASAKI; et al.
Abstract: Wide‐bandgap, layered hexagonal boron nitride (h‐BN) possesses excellent electrical insulation and ultrahigh thermal conductivity simultaneously, offering a perfect candidate for the growing demands of heating dissipations in modern chip industries and power electronics. Hybrids of h‐BN with polymers fulfill the thermal management materials (TMMs) requirement of flexibility, while the composite poses severe challenges in the interfacial bonding and excess thermal resistance. To date, the practical bonding between h‐BN intrinsic surfaces and polymer matrices remains elusive. This work reports on the effective alignment of h‐BN micro‐lamellae by introducing nitrogen‐atoms‐containing polymers as inter‐lamellae bridging mediums. Based on theoretical calculations the hydrogen bonding between polymer chains and the BN surface is revealed by differential charge densities mapping. It is shown experimentally that the neuron‐like polymer bundles strongly bonding surfaces of two neighboring h‐BN platelets as direct, microscopic evidence of the structure models. An extra alignment of h‐BN induced by this strong interfacial interaction leads to a higher degree of h‐BN stacking order, boosting the thermal conduction by eight times. These results reveal one unprecedented method to non‐covalently functionalize the h‐BN surface and expand the TMMs family in the dimension of the filler size, paving the way for exploring the larger‐sized ceramic TMMs. Abstract : One surface functionalization method is developed for hexagonal boron nitrides by utilizing the hydrogen bonding between nitrogen‐containing polymer and BN surface, which is corroborated by theoretical calculations. Neuron‐like polymer bundles strongly bond surfaces of two neighboring h‐BN micro‐platelets, leading to the incredible flexibility of ultrahigh thermal conductive papers even with ultrahigh BN contents (≈89 wt%).